Low-intensity anomaly involving ML≥4 events preceding strong earthquakes in Tibet - Gao, Jinrui; Zhu, Ye; Ji, Yingfeng; Zhu, Weiling; Qu, Rui; Li, Jiaji; Xu, Liang; Xie, Chaodi (Frontiers in Earth Science, 2023)
Seismic quiescence or enhanced phenomena are anomalous changes against the background of normal seismic activity. Preliminary studies have found that earthquakes with a magnitude of ML≥4 often occur at a low occurrence frequency before giant earthquakes in Tibet. This study analyzed the catalog of ML≥4 earthquakes from 2008 to 2022 and examined the anomalous occurrence of ML≥4 earthquakes preceding most ML≥6 earthquakes. When the monthly occurrence frequency of ML≥4 earthquakes was lower than 4 times over 6 consecutive months, the subsequent occurrence of ML≥6 earthquakes was highly likely as evidenced by observations. The anomalous characteristics of low-intensity activities were analyzed as a medium- and short-term prediction index for large earthquakes in the Tibetan area.